Ministry of Water and Housing - (:unkn) unknown (My University, 2011)
THE MINISTRY'S VISION "To provide and facilitate an environment in which potable water and affordable shelter will become a reality in the aspirations of a developing Jamaica." THE MINISTRY'S MISSION "The Ministry is committed (over the next ten years) to develop and implement policies and to effectively administer programmes for potable water and affordable housing solutions and to maintain a high quality through continuous training, good work environment while keeping abreast with technology to secure a better Jamaica."
Keywords: Water, Settlements